2020
DOI: 10.1111/1756-185x.13796
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of Achilles tendon: Is there any difference between ankylosing spondylitis, non‐radiographic axial spondyloarthropathy and controls?

Abstract: Purpose:The aim is to evaluate Achilles tendon enthesopathy with ultrasound (US) in ankylosing spondylitis (AS) and non-radiographic axial SpA (nr-axSpA) patients and controls, and compare these groups in terms of associations between disease activity parameters and ultrasonographic Achilles enthesitis signs. Methods:A total of 24 AS and 20 nr-axSpA patients fulfilling the Assessment in Spondyloarthritis International Working Group criteria for axSpA and 30 controls were enrolled. Demographic characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…More entheseal areas were evaluated and more information was gathered. In the present study, the entheses included the upper limbs, lower limbs, trunk, and ACW, whereas most studies have only focused on the upper and lower limbs [13][14][15]. The ndings of the present study have shown that the three entheses of AT, SCJ, and CCJ were more common in the AS group compared to the control group.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…More entheseal areas were evaluated and more information was gathered. In the present study, the entheses included the upper limbs, lower limbs, trunk, and ACW, whereas most studies have only focused on the upper and lower limbs [13][14][15]. The ndings of the present study have shown that the three entheses of AT, SCJ, and CCJ were more common in the AS group compared to the control group.…”
Section: Discussionmentioning
confidence: 61%
“…However, there is no clear agreement on which sites should be evaluated for enthesitis. Most studies have focused on the lower limbs [11,13,14], while some others investigated the upper limbs [15,16]. However, few articles pay attention to the anterior chest wall (ACW) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although HLA-B27 positivity among the Turkish patients diagnosed with AS has been investigated before, this is the first study evaluating the HLA-B27 positivity among the patients with AS and nr-axSpA in Turkey. [11][12][13][14] The fact that nr-axSpA patients were included in our analysis is the strength of our study. However, it is known that the different subtypes (HLA B2705, B2701, B2703, B2707, B2708, B2710, B2713, B2714, B2715, B2719 and B2725) and its distribution differ in terms of geography.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although there are studies regarding the HLA-B27 prevalence in patients with AS in Turkey, there is insufficient information on the HLA-B27 prevalence in patients with nr-axSpA. [11][12][13][14] Therefore, in this study, we aimed to evaluate; (1) the prevalence of HLA-B27 positivity among patients with AS and nr-axSpA, and (2) its association with disease activity, which was evaluated through the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score with C-reactive protein (ASDAS-CRP).…”
mentioning
confidence: 99%
“…Whether and to what extent US can distinguish between enthesitis of different origins including local non-inflammatory conditions needs to be established [144][145][146][147][148][149][150][151][152][153].…”
Section: Differential Diagnosismentioning
confidence: 99%